2018
DOI: 10.1007/s00264-018-4203-5
|View full text |Cite
|
Sign up to set email alerts
|

Management of Paprosky type three B acetabular defects by custom-made components: early results

Abstract: Our study aims at the evaluation of the recently introduced Lima Promade custom-made acetabular device for the treatment of complex acetabular Paprosky 3B defects. MethodsBetween 2016 and 2018, eight patients with major acetabular osteolysis and multiple revisions history were treated with a custom-made implant in a single centre and by a single surgeon. We assessed patients' demographics, peri-operative data, and complications and a specific questionnaire was submitted to the surgeon after each procedure. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 27 publications
(28 reference statements)
0
25
0
Order By: Relevance
“…However, they did not investigate the position compared to the contralateral side. Others reported satisfying final position of the implants, inclination of the shell or osseointegration, but did not investigate offsets and COR [ 28 , 29 ]. A recently published study by Walter et al showed significant lateralisation and cranialization when CTAC was used [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, they did not investigate the position compared to the contralateral side. Others reported satisfying final position of the implants, inclination of the shell or osseointegration, but did not investigate offsets and COR [ 28 , 29 ]. A recently published study by Walter et al showed significant lateralisation and cranialization when CTAC was used [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, they did not investigate the position compared to the contralateral side. Others reported satisfying nal position of the implants, inclination of the shell or osseointegration, but did not investigate offsets and COR (28,29). A recently published study by Walter et al showed signi cant lateralisation and cranialization when CTAC was used (30).…”
Section: Discussionmentioning
confidence: 99%
“…When the failure of hip arthroplasty causes big acetabular defects, custom-made components promise good solutions with low complication rate [15]. Also, 3D-printed custom-made prostheses represent a promising reconstructive technique, both in musculoskeletal oncology and in challenging revision [16].…”
Section: Hipmentioning
confidence: 99%